Degenerated oocyte in the cohort adversely affects IVF outcome - Yuval Atzmon; Mediea Michaeli; Diana Poltov; Nechami Rotfarb; Oshrit Lebovitz; Nardin Aslih; Einat Shalom-Paz (BMC, 2020)
Abstract The presence of Degenerated Oocyte (DEG) was mostly described after intracytoplasmic sperm injection (ICSI), with fewer reports on DEG at the time of ovum pick-up (OPU). This study aims to assess morphokinetics of embryos cultured in a time-lapse incubator and compare cohorts with and without DEG at OPU. In a retrospective cohort study from January 1, 2016 until September 31, 2017 a total of 399 IVF/ICSI cycles and 2980 embryos were evaluated. In 81 of 399 cycles at least one DEG oocyte was observed at the time of OPU. The remaining 318 cycles with no DEG oocyte were compared as a control group. In the DEG group, significantly more oocytes were collected per patient (12.9 ± 7.2 vs. 10.1 ± 6.1. P < 0.001). Fertilization rate, pregnancy and clinical pregnancy rates were comparable between the two groups, however, the morphokinetics and developmental scores of the embryos were significantly worse in the DEG group, (KID 3.4 ± 1.6 vs. 3.2 ± 1.6 P = 0.002 and ESHRE 1.5 ± 1.1 vs. 1.4 ± 1.0 P = 0.046). Significantly more patients achieved top-quality embryos in the NON DEG group (58.8% vs. 53.0%, P = 0.03), however, comparable delivery rate was achieved in both groups. In the DEG group, the frequency of DEG oocyte per cycle was negatively correlated with pregnancy rate. GnRH agonist protocol and the 17-20G needle used for OPU were significant predictors for the presence of DEG oocyte at OPU. In conclusions DEG oocyte may negatively affect IVF outcome, however, younger patients, and significantly more oocytes collected in the DEG group compensate for the IVF results.